Islamic Learning Method (ILM) to Shape Students' Character and Understanding of National Values In Islamic Schools at Banten Region - Nur Afif; Asrori Mukhtarom; Agus Nur Qowim (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Every young generation must have a character that understands the values of the nation and state. Things students must be formed in a religious character in Islamic education. This study aims to examine the application of the Islamic Learning Model (MIL) to improve learning in understanding the values of the nation and state in shaping the character of students in Islamic schools in the Banten region. The approach used in this study is a qualitative approach. The type of research used in this research activity is field research. Based on the results of the study it was found that the Islamic Learning Method (ILM) method can be applied to shape students' character and understanding of Islamic values in Banten Regional Islamic Schools. The ILM method is carried out by teaching and character building according to the teachings of Islamic values. Activities carried out in improving coaching in schools so that changes in student behavior in committing violations such as discipline are decreasing and the existence of coaching in the form of an Islamic learning model will improve character and understand Islamic values in everyday life.